Plan piloto para el desarrollo agro-industrial del cultivo de la yuca en algunos departamentos de la Costa Atlantica de Colombia : Tercer informe junio 1983-junio 1984 - Best, R. (International Center for Tropical Agriculture, 1984)
The 1st yr of operation (1983-84) of 6 cassava natural drying plants, established in some states of the Colombian Atlantic Coast as a result of the successful operation of the Betulia pilot plant (Sucre) established in 1981, is reported. Under the present production and commercialization conditions, the natural drying process of cassava proved to be an economically profitable activity in the region; however, it was sensitive to fresh root price and the degree of drying plant occupation. The major constraint to increased cassava yields is the lack of programs to produce healthy seed. In regional trials, var. CM 681-2, M Col 22, and M Col 1505 performed similarly or superior to the local var. Venezolana. Studies conducted on agricultural production and marketing in the region indicated that adequate conditions exist for cassava agroindustrialization, especially because of the stagnation of cereal grain production for the animal feed industry and, on the other hand, the reduced demand of fresh roots. Ten new drying plants (3 in Cordoba, 2 in Sucre, 1 in Bolivar, 2 in Atlantico, 2 in Magdalena, and 1 in Cesar) will be established in the second semester of 1984. (CIAT)